Rhabdomyolysis as a rare complication of bariatric surgery - Usta, Sertac; Karabulut, Koray (Turkish Surgical Assoc, 2021)
Rhabdomyolysis after bariatric surgery is a quite rare occurrence with low recognition. Due to the breakdown of striated muscle fibers, creatine kinase and myoglobin are released into systemic circulation with variable effects on renal filtering functions. Herein, it was aimed to present a patient who developed rhabdomyolysis following revision bariatric surgery. This 34-year-old male patient was admitted for bariatric surgery. He had had a gastric band surgery approximately six years ago, with regain of weight starting one year after surgery gradually reaching the previous weight level. Consequently, the gastric band had been removed with open surgery three years ago. The patient had a body mass index of 69 kg/m(2) as well as an incisional hernia due to previous surgery. Although initially laparoscopic sleeve gastrectomy was planned, a switch to open surgery was made due to the presence of diffuse intra-abdominal adhesions and giant incisional hernia precluding laparoscopic intervention. The total duration of surgery was 420 minutes. Postoperative laboratory work-up showed elevated blood creatine kinase (25837 U/L). Upon the failure of fluid replacement and diuretics, hemodialysis was initiated at postoperative day 1. Despite daily sessions of hemodialysis, acidosis did not improve, his general status worsened and the patient died on postoperative day 14. Rhabdomyolysis is a severe and potentially life-threatening complication of bariatric surgery. Its severity may vary from asymptomatic elevations of creatine kinase to death. Postoperative creatine kinase levels should be routinely checked in high-risk patients as a practical and inexpensive laboratory modality for early diagnosis.
Bariyatrik cerrahinin nadir bir komplikasyonu rabdomiyoliz
Keywords: Sleeve gastrectomy; rhabdomyolysis; complication